2022
DOI: 10.3390/ijerph191710915
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphism rs1799732 of DRD2 Dopamine Receptor Gene and Personality Traits among Cannabis Dependency

Abstract: Compared to other addictive substances, patients with cannabis addiction are significantly outnumbered by those who report dependence on other, more addictive substances. Unfortunately, most cannabis addiction goes untreated, and among those who choose treatment, the requirements are much higher for adolescents and young adults. The aim of the study: To examine the relationship of cannabinoid dependency in the genetic context—the association between the rs1799732 polymorphism of the DRD2 gene and psychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…The Mini-International Neuropsychiatric Interview is a structured diagnostic interview used to evaluate psychiatric diagnoses according to DSM-IV and ICD-10 criteria. The Personality Inventory (NEO-FFI Five-Factor Inventory, NEO-FFI) contains six components for each of the five traits—neuroticism (anxiety, hostility, depression, self-awareness, impulsivity, susceptibility to stress), extroversion (warmth, sociability, assertiveness, activity, emotion seeking, positive emotions), openness to experience (fantasy, aesthetics, feelings, actions, ideas, values), agreeableness (trust, straightforwardness, altruism, compliance, modesty, tenderness), and conscientiousness (competence, order, duty, striving for achievements, self-discipline, consideration) [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…The Mini-International Neuropsychiatric Interview is a structured diagnostic interview used to evaluate psychiatric diagnoses according to DSM-IV and ICD-10 criteria. The Personality Inventory (NEO-FFI Five-Factor Inventory, NEO-FFI) contains six components for each of the five traits—neuroticism (anxiety, hostility, depression, self-awareness, impulsivity, susceptibility to stress), extroversion (warmth, sociability, assertiveness, activity, emotion seeking, positive emotions), openness to experience (fantasy, aesthetics, feelings, actions, ideas, values), agreeableness (trust, straightforwardness, altruism, compliance, modesty, tenderness), and conscientiousness (competence, order, duty, striving for achievements, self-discipline, consideration) [ 53 ].…”
Section: Methodsmentioning
confidence: 99%
“…It is well known that addictive drugs increase DA release, but current knowledge suggests that the problem is more complex and cannot be limited to dopaminergic activation. It has been found that the C957T polymorphism (SNP: rs1799732), located in exon 7 of DRD2 (gene map locus 11q23), alters the availability of DRD2 and that a higher frequency of the CC genotype is associated with a higher risk of alcoholism [10,11], nicotine dependence [12], and cannabis dependence [13]. In addition, other studies have found that the NTRK3 rs2229910 gene is a genetic variant that is significantly associated with online gaming disorder [14].…”
Section: Introductionmentioning
confidence: 99%